Теплостойкий наполнитель "Премикс" – химический состав и свойства - Уберман, В. И.; Васюков, А. Е.; Полосухина, Л. А.; Карташев, В. В.; Касимов, А. М.; Александров, А. Н.; Васьковец, Людмила Антоновна (НТУ "ХПИ", 2010)
Chemical composition and properties of 42 samples of «thermo resisted filling substance under the name "Premix"» (TFP), which imported from Hungary during 1995 – 2005 years, investigated. TFP is dry mixture of small solid particles declared as material for brake blocks manufacturing. It is determined that TFP belongs neither to thermo-resisted (for middle and hard regime of friction) nor to mostly mineral mixtures. TFP includes more than 80 organic substances, which usual for manufacturing of plastic and rubber wares. All samples are sufficiently heterogeneous, very different by chemical components and do not generated by single technological origin
Keywords: минеральные вещества; системы торможения; экспертиза состава